Effects of antifungal treatment on the embryonic development, hatching, and larval survival of Clarias gariepinus (Burchell, 1822) - Mun, Kelvin Leong Wai (2013)
A study on the effect of different antifungal agents on the embryonic development, hatching and survival of African catfish, Clarias gariepinus was carried out from April to August 2013. Eggs and sperms of C. gariepinus was produced through induced breeding technique using ovaprim hormone. Eggs were fertilized using dry method. Newly fertilized eggs were treated for 24 hours with different dosages of formalin, chamomile extract and methylene blue at incubation temperature of 27±1˚C. Embryonic development was monitored at hourly intervals for 24 hours. Formalin treatment at 15, 30 and 45 ppm showed the highest percentage of hatching (p<0.05), of 59, 57, and 58% respectively as compared to other treatments. However, this treatment produced the highest numbers of deformed larvae (p<0.05). In contrast, treatment using chamomile produced the lowest numbers of deformed larvae (p<0.05). This study showed that formalin is the most effective anti-fungal treatment, evident with the highest percentage of hatching. However consideration on safety and environmental issues need to be given attention. Second best alternative is using chamomile extract as antifungal for the eggs of C. gariepinus. Fungal growth was observed as early as 15 hours after fertilization. Overall, all the anti-fungal treatments used in this study do not affect the development C. gariepinus embryos.